METHANE DISCHARGE INTO THE BLACK SEA AND THE GLOBAL OCEAN VIA FLUID FLOW THROUGH SUBMARINE MUD VOLCANOES - Wallmann K.; Drews M.; Aloisi G.; Bohrmann G. (My University, 2006)
During the MARGASCH cruise M52/1 in 2001 with RV Meteor we sampled surface sediments from three stations in the crater of the Dvurechenskii mud volcano (DMV, located in the Sorokin Trough of the Black Sea) and one reference station situated 15 km to the northeast of the DMV. We analysed the pore water for sulphide, methane, alkalinity, sulphate, and chloride concentrations and determined the concentrations of particulate organic carbon, carbonate and sulphur in surface sediments. Rates of anaerobic oxidation of methane (AOM) were determined using a radiotracer (14CH4) incubation method. Numerical transport-reaction models were applied to derive the velocity of upward fluid flow through the quiescently dewatering DMV, to calculate rates of AOM in surface sediments, and to determine methane fluxes into the overlying water column. According to the model, AOM consumes 79% of the average methane flux from depth (8.9 · 10+ 6 mol a- 1), such that the resulting dissolved methane emission from the volcano into the overlying bottom water can be determined as 1.9 · 10+ 6 mol a- 1. If it is assumed that all submarine mud volcanoes (SMVs) in the Black Sea are at an activity level like the DMV, the resulting seepage represents less than 0.1% of the total methane flux into this anoxic marginal sea. The new data from the DMV and previously published studies indicate that an average SMV emits about 2.0 · 10+ 6 mol a- 1 into the ocean via quiescent dewatering. The global flux of dissolved methane from SMVs into the ocean is estimated to fall into the order of 10+ 10 mol a- 1. Additional methane fluxes arise during periods of active mud expulsion and gas bubbling occurring episodically at the DMV and other SMVs. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANAEROBIC OXIDATION OF METHANE; BLACK SEA; METHANE FLUXES; NUMERICAL MODELLING; SUBMARINE MUD VOLCANOES